Feedback linearization of an active magnetic bearing system operated with a zero-bias flux - Mystkowski, Arkadiusz; Kaparin, Vadim; Kotta, Űlle; Pawluszewicz, Ewa; Tonso, Maris (Zielona Góra: Uniwersytet Zielonogórski)
Input-output linearization by state feedback is applied to a flux-controlled active magnetic bearing (AMB) system, operated in the zero-bias mode. Two models of the AMB system are employed. The first one is described by the third-order dynamics with a flux-dependent voltage switching scheme, whereas the second one is the fourth-order system, called self-sensing AMB, since it does not require the measurement of the rotor position. In the case of that system we had to find the flat outputs to guarantee its stability. The proposed control schemes are verified by means of numerical simulations performed within the Matlab environment.
Keywords: active magnetic bearing; flux control; zero-bias; feedback linearization; flat outputs